2018
DOI: 10.3390/molecules23102667
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Antiradical Activity of Polyphenols from Lotus Seed Epicarp by Probiotic Bacteria Bioconversion

Abstract: Probiotic bacteria is able to metabolize polyphenols and produce functional compounds. In this study, we investigated the ability of probiotic bacteria including Lactobacillus, bifidobacteria and Enterococcus strains to increase the antioxidant capacity of polyphenols from lotus seed epicarp (PLSE) at full ripening stage. The results showed that the six selected strains of probiotic bacteria grew well in De Man, Rogosa and Sharpe (MRS) broth with PLSE, and their resistant extent to PLSE varied from strain to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…In this research, quercetin and kaempferol were detected in EA and ET lotus petal extracts, similar to [2], which reported both polyphenols in lotus flower extracts. Nevertheless, similar to this research, alkaloids, flavonoids, and steroids were reported in extracts of lotus leaves [4,6,8], seed [2,9], embryo/plumule [2,7], and root [3]. Importantly, no previous research documented the presence of chlorogenic acid, ferulic acid, and coumarin in extracts of lotus parts [2][3][4][5][6][7][8][9].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In this research, quercetin and kaempferol were detected in EA and ET lotus petal extracts, similar to [2], which reported both polyphenols in lotus flower extracts. Nevertheless, similar to this research, alkaloids, flavonoids, and steroids were reported in extracts of lotus leaves [4,6,8], seed [2,9], embryo/plumule [2,7], and root [3]. Importantly, no previous research documented the presence of chlorogenic acid, ferulic acid, and coumarin in extracts of lotus parts [2][3][4][5][6][7][8][9].…”
Section: Discussionsupporting
confidence: 80%
“…Nevertheless, similar to this research, alkaloids, flavonoids, and steroids were reported in extracts of lotus leaves [4,6,8], seed [2,9], embryo/plumule [2,7], and root [3]. Importantly, no previous research documented the presence of chlorogenic acid, ferulic acid, and coumarin in extracts of lotus parts [2][3][4][5][6][7][8][9].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Liu et al (2018a) reported that the major bioactive metabolites for the antioxidative activity of PMB of polyphenol compounds contained epicatechin, catechin, caffeic acid, chlorogenic acid, and hyperoxide. Moreover, Lactobacillus reuteri and Enterococcus faecalis showed a high bioconversion rate and high anti-radical activity, which might have excellent potential for PMB (Liu et al, 2018a). The pharmacological effects of PMB are also well known.…”
Section: Classification Of Pmbmentioning
confidence: 99%
“…Liu, et al [17] reported that polyphenols from lotus seed epicarp at three different ripening stages have good anti-radical abilities, and they identified some phenolic compounds from lotus seed epicarp. Recently, Liu, et al [18] found that the anti-radical activity of polyphenols from lotus seed epicarp increases by probiotic bacteria bioconversion. Yan, et al [19] reported that polyphenols from lotus seed epicarp have antiproliferation ability on human hepatoma G2 (HepG2) cells.…”
Section: Introductionmentioning
confidence: 99%